Soeurs de la Charité de Jesus et de Marie : 100 ans au Zaïre 1892-1992. - Zana Aziza Etambala, Matthieu; Valsala; Herman, Mariette (S.l. : s.n., 1992)
Liste des Missionaires au Congo, alfabetique, fait en 1992